2020
DOI: 10.1186/s12199-020-00887-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and related influencing factors among rural elderly in 14 poverty state counties of Chongqing, Southwest China: a cross-sectional study

Abstract: Background China has the largest elderly population in the world; little attention has been paid to the mental health of elderly in areas of extreme poverty. This is the first study to investigate the mental health of the rural elderly in poverty state counties in Chongqing and was part of the Chongqing 2018 health literacy promotion project. Methods In 2019, a cross-sectional study was conducted to investigate the mental health status of the rural elderly in fourteen poverty state counties of Chongqing, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Among the participants, people aged 60-64 were more likely to suffer from mental issues, which seemed inconsistent with the previous studies (26,35,36). A cross-sectional study showed that with the increase of age, the demand for long-term service may bring the elderly a greater economic burden and the burden of being taken care of (26). But the other point of view is that the younger elderly have to face the big change and transition of social roles and the decline of socio-economic status because of the retirement (37).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Among the participants, people aged 60-64 were more likely to suffer from mental issues, which seemed inconsistent with the previous studies (26,35,36). A cross-sectional study showed that with the increase of age, the demand for long-term service may bring the elderly a greater economic burden and the burden of being taken care of (26). But the other point of view is that the younger elderly have to face the big change and transition of social roles and the decline of socio-economic status because of the retirement (37).…”
Section: Discussioncontrasting
confidence: 87%
“…Therefore, more humanistic care and social support is needed to protect this special population. Among the participants, people aged 60-64 were more likely to suffer from mental issues, which seemed inconsistent with the previous studies (26,35,36). A cross-sectional study showed that with the increase of age, the demand for long-term service may bring the elderly a greater economic burden and the burden of being taken care of (26).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Analogous with previous studies, a cut-off score of >15 and >21 and >29 was used to identify individuals displaying a likelihood of mild, moderate, and severe psychological distress. 53,54 The K10 has good reliability, and the Cronbach's α in this study was 0.953.…”
Section: Dependent Variable: Psychological Distressmentioning
confidence: 48%
“…An older adult who lives alone is someone who never had or no longer has a partner, spouse, or child who resides in their home 2 . As a result of the increase in average life expectancy, declining fertility rates, young adults moving from rural areas to cities after marriage, differences in lifestyle and life concepts between older adults and their children, leading to older adults staying in their original rural residence, the number of rural older adults living alone has steadily increased in China 3 . Older adults living alone is becoming the main family structure in rural China.…”
Section: Introductionmentioning
confidence: 99%